Climate Change Adaptability Among Younger and Older Fishermen on the North Coast of Madura Island (Faculty of Fisheries and Marine Science, Brawijaya University, 2025)
Climate change has introduced new challenges for fishers, particularly through shifting weather patterns and changing ocean conditions that directly affect fishing activities. This study analyzes the differences in adaptive capacity between younger and older fishermen, as well as the role of intergenerational collaboration in shaping adaptation strategies. Age remains a subject of debate regarding its influence on technology adoption. This study used a simple random sampling method to select the fishermen samples in Banyusangkah Village and Pasongsongan Village. The sample size was determined using the Slovin formula, resulting in a sample of 217 respondents. Data analysis was conducted using an independent t-test with the Stata 14 software to compare the adaptive capacity of younger and older fishermen to climate change. The analysis showed significant differences in adaptive capacity between the two groups. Older fishers rely more on experiential knowledge in dealing with changes in weather and sea conditions, while younger fishers tend to be more adaptive in using new technology and modern methods.